(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Ehlers-Danlos syndrome (EDS) is a heterogeneous group of rare inherited diseases involving connective tissue. Vascular EDS (vEDS) is associated with abnormal type III collagen, which is an essential component of skin, hollow organs and arterial walls, and causes potentially fatal visceral and arterial complications. The surgical management of these patients is challenging and should be limited to life-saving procedures. CASE DESCRIPTION We report a case of a 42-year-old male who presented a hemorrhagic shock due to spontaneous rupture of an ascending branch of the left colic artery. The coexisting presence of multiple abdominal vascular abnormalities suggested the diagnosis of vEDS, later confirmed by the discovery of a new missense mutation in the COL3A1 gene with pathogenic significance. The post-operative course was marked by a mechanical ileus caused by an ischemic stenosis of the descending colon. Failure of conservative management and the well-known risk of colonic perforation in these patients led to the decision to perform a diverting ileostomy. CONCLUSION The management of these patients is difficult, and risk-benefit assessments must be made on a case-by-case basis. Less invasive procedures should be considered whenever possible.